Even after armed conflict, the environmental quality of Indigenous Peoples' lands in biodiversity hotspots surpasses that of non-Indigenous lands - Beattie, M.; Fa, J.E.; Leiper, I.; Fernández-Llamazares, Á.; Zander, K.K.; Garnett, S.T. (Elsevier, 2023)
Indigenous Peoples lands cover over a fifth of the world's land surface and support high levels of biodiversity. However, for centuries Indigenous Peoples have suffered from deprivation, often dispossession, and even cultural genocide, a process continuing today in some regions. Biodiversity hotspots, global areas of high endemicity that are heavily threatened by habitat loss and other human activities are also affected by conflict. Although covering only 2.4 % of the world's surface, over 80 % of armed conflicts occurred in biodiversity hotspots between 1950 and 2000. Given that many hotspots overlap with Indigenous Peoples' lands, we asked whether the co-occurrence of Indigenous Peoples' lands and high ecological integrity, measured by using Intact Forest Landscapes as units which still contain significant biological diversity, and the Human Footprint as a proxy for anthropogenic impacts, increased the persistence of biodiversity in hotspots where there has been armed conflict. Our results show that, within biodiversity hotspots, armed conflict was more likely to occur on Indigenous Peoples' lands than non-Indigenous lands, yet environmental damage and anthropogenic impacts were both lower. We suggest that Indigenous Peoples have been able to moderate ecosystem degradation processes before, during, and after armed conflict because of their strong ties to their lands and their determination to defend their rights and territories. We argue that recognition and support for the efforts of Indigenous Peoples to protect their lands is not only socially just but also essential for meeting the now pressing global post-2020 conservation targets.